Degradation of Methylene Blue by a Photo-Fenton System Based on Copper Ferrite Catalyst and Ascorbic Acid - Adika Nuzula; Indang Dewata; Desy Kurniawati; Jon Effendi (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Water pollution caused by methylene blue is difficult to treat due to its stability and resistance to conventional methods. This study aims to evaluate the performance of a CuFe₂O₄-based photo-fenton system enhanced with ascorbic acid. The catalyst was synthesized using the sol–gel method and characterized by FTIR and XRD. Degradation experiments were carried out under UV irradiation (5 W) by varying pH (1–9) and H₂O₂ concentration (1.5–15 mmol/L). Methylene blue concentration was measured using a UV–Vis spectrophotometer at a wavelength of 664 nm. The results show that degradation efficiency reached 98.48% at pH 3 and 10 mmol/L H₂O₂. This condition promotes efficient Fe²⁺ activation of H₂O₂ to generate hydroxyl radicals (•OH), while ascorbic acid accelerates the reduction of Fe³⁺ to Fe²⁺, sustaining the redox cycle and increasing radical availability. These findings demonstrate that the system is effective and has strong potential for wastewater treatment.